Causes of sick leave, disability pension, and death following a breast cancer diagnosis in women of working age. (June 2019) - Plym, Anna; Johansson, Anna L.V.; Bower, Hannah; Voss, Margaretha; Holmberg, Lars; Fredriksson, Irma; Lambe, Mats
Abstract: Objectives: Women diagnosed with breast cancer during working age are at increased risk of permanent absence from work, but the underlying medical causes have rarely been studied. We examined the risk of cause-specific sick leave, disability pension, and the competing event death after a breast cancer diagnosis in a population-based cohort study. Materials and methods: From the Breast Cancer Data Base Sweden, we identified 16, 603 women diagnosed with stage I-III breast cancer between 2000 and 2012, and 63, 773 control women. Using multi-state modelling, we calculated probabilities and durations of sick leave, disability pension, and death by registered cause, together with cause-specific hazard ratios. Results: Five years after diagnosis, causes other than cancer accounted for around half of all sick leave (3.5% out of 6.8% of women) and disability pension (1.4% out of 2.6%) in women with breast cancer. Compared with control women, women with breast cancer were at increased risk of sick leave and disability pension due to mental disorders (HR 1.24, 95% CI 1.15–1.33 and HR 1.54, 95% CI 1.29–1.85, respectively) and disability pension due to inflammatory diseases (HR 1.46, 95% CI 1.05–2.03). The risk of sick leave and disability pension due to cardiovascular disease was also elevated, although only statistically significant for disability pension in women diagnosed after 2005 (HR 2.24, 95% CI 1.22–4.13). Conclusion: Follow-up, support, and rehabilitation programs for women diagnosed with breast cancer must address a wide range of psychological and physical conditions to limit the consequences on working life. Highlights: Causes other than cancer accounted for half of all absence from work in year five. Absence because of mental disorders was more common in women with breast cancer. Cardiovascular and inflammatory diseases were also more commonly reported causes. Other causes of absence were lymphedema and fatigue-related conditions.